Individual Taxpayers’ Compliance Moderated By Taxpayers’ Awareness - Indah Wahyuni; Hari Setiyawati (International Journal of Social Science and Business, 2023)
Taxes are fundamental for the running the government because tax revenue is the largest source of state revenue, raching 80% and the directoral general of taxes continue to the government as a provider of public services needed by the community must be responsible and continue to strive to provide the best service for the sake of improving public services. On the other hand, community satisfaction is a measure of the success of public services provided by public service providers. This study aims to measure the quality of tax authorities' services and tax sanctions on taxpayer compliance and awareness of individual taxpayers. The data was collected through survey on 100 individual taxes payers. The analysis technique used is SEM. The results showed that tax service quality has a positive and significant effect on taxpayer compliance. Tax sanctions have a positive and significant effect on taxpayer compliance. Taxpayer awareness is able to moderate the influence of tax authorities' service quality on taxpayer compliance. Taxpayer awareness is able to moderate the effect of tax sanctions on taxpayer compliance. This means that the existence of tax sanctions increases taxpayer compliance.